COINCIDENCES OF FIBREWISE MAPS BETWEEN SPHERE BUNDLES OVER THE CIRCLE - Goncalves, Daciberg L.; Koschorke, Ulrich; Libardi, Alice Kimie Miwa [UNESP]; Neto, Oziride Manzoli (Cambridge Univ Press, 2014)
When can two fibrewise maps be deformed in a fibrewise fashion until they are coincidence free? In order to get a thorough understanding of this problem (and, more generally, of minimum numbers that are closely related to it) we study the strength of natural geometric obstructions, such as omega-invariants and Nielsen numbers, as well as the related Nielsen theory.In the setting of sphere bundles, a certain degree map deg(B) turns out to play a decisive role. In many explicit cases it also yields good descriptions of the set F of fibrewise homotopy classes of fibrewise maps. We introduce an addition on F, which is not always single valued but still very helpful. Furthermore, normal bordism Gysin sequences and (iterated) Freudenthal suspensions play a crucial role.
Keywords: fibrewise map and homotopy; coincidence; Nielsen number; sphere bundle; normal bordism; Gysin sequence